Community structure and monthly dynamics of zooplankton in high altitude rice fish system in Eastern Himalayan region of India - Saikia Rajashree; Das Tapati; Gogoi Budhin; Kachari Akash; Safi Vivekanand; Das Debangshu N (International Journal of Life Sciences, 2017)
The community structure and seasonal dynamics of zooplankton were examined in high altitude rice fish system of Eastern Himalaya. The study was conducted at fortnight interval from field preparation to harvesting of rice during two seasons of 2013 and 2014. All the standard procedures were followed to obtain relevant quantitative and qualitative data on zooplankton showing, a total of five major communities of zooplankton viz., Cladocera, Copepoda, Rotifera, Protozoa, and Ostracoda were encountered. These comprised of 33 taxa of Cladocera, 11 taxa of Copepoda, 17 taxa of Rotifera, 5 taxa of Protozoa and only one taxon of Ostracoda. Cladocera was the most dominant (29%) while Rotifera (12%) was least abundant. Density of zooplankton communities showed significant (p<0.05%) monthly variation during the rice growing seasons. The computed diversity indices confirmed the presence of diversified zooplankton in the rice fish system. Month wise cluster of similarity index revealed very close species composition at initial and mid phases compared to end phase of the rice growing season. The zooplankton therefore becomes natural food sources of fishes concurrently in the flooded rice fields to enhance unit land productivity.